Surgical approaches to tumors and epileptogenic zones close to Wernicke's area - Cukiert,Arthur (1995)
Surgical procedures near to language related brain regions may cause severe morbidity in relation to speech. Operations performed under local anesthesia and intraoperative cortical mapping may minimize these risks. Six patients with tumors near the Wernicke's area were treated (2 low-grade astrocytomas, 1 ganglioglioma, 1 xanthoastrocytoma, 1 metastasis, 1 glioblastoma). Their clinical presentation consisted of epilepsy (n=4) and dysphasia (n=2). The skin and periosteum were infiltrated with local anesthetic and an ample craniotomy was performed. Cortical stimulation with an unipolar electrode was then carried out with concomitant speech testing (mainly comprehension and sequential speech). After mapping, the best surgical approach aiming to avoid the mapped area was elected. In 5 cases the resection was total and in 1, partial (glioblastoma). There was a transitory (10 days) worsening of the pre-operative deficit in 1 case (glioblastoma). In 3 patients, the speech areas were displaced: posteriorly (n=2) or anteriorly (n=l). Surgical procedures under local anesthesia are safe and may avoid post-operative language disturbances in patients with tumors near to Wernicke's area.